Enteric listeriosis in grazing steers supplemented with spoiled silage - Garcia, Juan Angel; Micheloud, Juan Francisco; Campero, Carlos Manuel; Morrell, Eleonora Lidia; Odriozola, Ernesto Raul; Moreira, Ana Rita (2017)
An outbreak of enteric listeriosis in steers that were fed spoiled silage is reported. The outbreak started 2 days after ~200 animals in a single paddock were given a supplement of spoiled silage. Forty animals (20%) were affected, and 13 (6.5%) died over a period of 10 days. Affected animals were recumbent, depressed, and had diarrhea with mucus and fibrin. Gross and microscopic findings in 3 animals that were subjected to autopsy included excess peritoneal fluid, congestion and edema of abomasum, suppurative enteritis and colitis, and suppurative mesenteric lymphadenitis. Two strains of Listeria monocytogenes were isolated, one of serotype 1/2c from the gallbladder and one of serotype 1/2b from the spoiled silage. Listeria monocytogenes was detected in the mesenteric lymph nodes and intestinal wall of 1 animal by immunohistochemistry (IHC). Clinical history and signs, gross and microscopic findings, bacterial isolation, and IHC results confirmed a diagnosis of enteric listeriosis. The source of infection was likely the spoiled silage